The meaning of “Emotion” (情) in Confucian philosophy - Tang, Yan (Dialog, 2024)
“Emotion” (情) is a very complex concept in Confucianism, but it can be interpreted in five dimensions. Interpreted as “innate instinct,” emotion refers to the cognitive attributes and physiological basis of emotion. Interpreted in terms of desire, it emphasizes the regulation and restriction of emotion. Construed in terms of Qi (氣), it indicates the source and path of emotion. The interpretation of emotion by nature (性) is most commonly used by Confucians and constitutes the fundamental position of Confucianism. Confucianism can both unify “nature” and “emotion” and also downgrade the status of emotion. The interpretation of emotion by Yin (陰) and Yang (陽) explains the nature and principle of emotion with the help of the rules of heaven. Ritual is based on emotional psychology, and the most basic emotional psychology of ethical life is the premise of Confucian social ritual.